2017
DOI: 10.18632/oncotarget.18097
|View full text |Cite
|
Sign up to set email alerts
|

Oleoylethanolamide inhibits α-melanocyte stimulating hormone-stimulated melanogenesis via ERK, Akt and CREB signaling pathways in B16 melanoma cells

Abstract: The present study aimed to examine the potential inhibitory activity of oleoylethanolamide (OEA) on α-melanocyte stimulating hormone (α-MSH)-stimulated melanogenesis and the molecular mechanism(s) involved in the process in B16 mouse melanoma cells. Our data demonstrated that OEA markedly inhibited melanin synthesis and tyrosinase activity in α-MSH-stimulated B16 cells. In addition, the expression of melanogenesis-related proteins, such as melanocortin-1 receptor (MC1R), microphthalmia-associated transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Furthermore, phosphorylation of CREB was significantly suppressed by BHCP. The regulation of α-MSH-induced CREB phosphorylation is known to be potentially important in regulating pigmentation [ 28 ]. These results indicate that the anti-melanogenic effects of BHCP result from the downregulation of MITF and tyrosinase via the downregulation of phosphorylated CREB.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, phosphorylation of CREB was significantly suppressed by BHCP. The regulation of α-MSH-induced CREB phosphorylation is known to be potentially important in regulating pigmentation [ 28 ]. These results indicate that the anti-melanogenic effects of BHCP result from the downregulation of MITF and tyrosinase via the downregulation of phosphorylated CREB.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase activity was estimated by measuring the rate of L-DOPA oxidation as previously described, with certain modifications ( 23 ). B16 cells were seeded in a 6-well plate at a density of 3×10 5 cells/well and allowed to attach for 12 h. Then, cells were treated with 1,5-diCQA at 0, 5, 50, 100 µ M or 8-MOP at 50 µ M for 24 h; SB203580 (10 µ M); PD98059 (1 µ M); or SP600125 (10 µ M) for 2 h prior to 1,5-diCQA application.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with these results, SP600125‐induced tyrosinase activity, and the pigmentation of cell pellets was also reduced by kazinol U (Figure D, E). It has been reported that ERK and p38 participate in melanogenesis via MITF and tyrosinase regulation (Bellei et al ., ; Baek and Lee, ; Zhou et al ., ). We found that kazinol U significantly increased p38 and ERK phosphorylation in B16F10 and SK‐MEL‐28 cells (Supporting Information Figure S6B,C).…”
Section: Resultsmentioning
confidence: 97%